A Study on Surface Roughness and Burr Formation of Al6061 with Different Spindle Speed and Federate for Small End Milling Cutter - Azuddin, M.; Abdullah, W. (International Journal of Integrated Engineering, 2009)
This paper reports the results of experiments to investigate surface roughness and burr formation during the slot milling of Aluminum 6061. The experiment was carried out with small cutting tool diameter and several of spindles speed and federate. Generally, cutting parameters will influence on surface roughness and the formation of burrs in small slot milling operations. Although it is not possible to avoid burr formation by modifying the cutting parameters, the burr size can be reduced by selecting the appropriate values. The results showed that slot milling with cutting tool with diameter 2.0mm and 3.0mm have a similar behavior for surface roughness with respect to federate and spindle speed. The larger cutting tool diameter results in a larger burr formed. Burr height increased due to larger chip load as the spindle speed increased. It also shown that Burr-breakage type of burr more significant in cutting AL6061